The moral Philosophy of Thomas Aquinas - Stančienė, Dalia Marija (Problemos, 2004)
The moral philosophy of Thomas Aquinas, discussed in this article, is titled as the Natural Law Ethics by many authors. This ethics could be characterized as the synthesis of the elements of Christian theology, Aristotelianism and neoplatonism. Aquinas divides law into eternal, divine, natural and human. He also mentions the fifth kind of law, the law of sin. The natural law, which is defined by Aquinas as the participation of the eternal law in rational creature, is the most important for ethics; for the main principles of human behaviour springs from it. The first of these principles is the precept: good is to be done and pursued, and evil is to be avoided. Human reason is able to find it independently, without any supernatural assistance. This precept is the first principle of Aquinas’ ethics. In relation with the natural inclinations it produces other four important precepts: human life is to be preserved and reproduced, man has to know truth about God and live in society. These precepts constitute the core of Aquinas’ ethics.
Keywords: moral philosophy; thomistic ethics; natural law; natural’s inclinations; reason